Algoritmo para detecção e localização de faltas em linha de transmissão de 230 kV mediante leitura de oscilografia com base na transformada Wavelet - Silva, Rodrigo Niederauer da (2024)
This work presents the development of an algorithm for fault analysis in 230 kV Transmission Lines (TL), aiming to identify the type of fault, the phases involved, and the estimated location of the fault. The algorithm processes oscillographic records of electrical events in the standard format Common Format for Transient Data Exchange (COMTRADE), widely used in power systems. To validate the algorithm, a real 230 kV TL was modeled, validated, and simulated in a computational environment, analyzing various fault scenarios with variations in location, incidence angle, and fault resistance. As a comparison tool, the ANÁLISE® software was used, a program for analyzing oscillographic records that estimates the fault location based on the comparison between the line impedance and the fault impedance. This approach, however, presents limitations in high-impedance fault cases, especially when only one terminal's records are available. The algorithm developed in this work aims to overcome these limitations. By using records from only one terminal, the identification and location of faults proved to be more efficient in various scenarios. The proposed methodology is based on the Wavelet Transform (WT), which allows the detection of abrupt energy variations in signals, both in the time and frequency domains. The results obtained indicate that the algorithm is effective and has potential for practical applications in real power transmission systems.